Changes in relative consumer prices and the substitution bias of the Laspeyres price index: Ireland, 1985-2001 - Somerville, R. A. (Economic & Social Studies, 2004)
This paper shows that Irish relative consumer prices have changed significantly, 1985-2001, at the ten commodity-group level. A ?true? cost-of-living index is derived from Madden?s (1993) parameter estimates for an Almost Ideal Demand System. Despite relative price changes, the substitution bias of a computed Laspeyres index is small, and the official Consumer Price Index tracks the computed index closely. Superlative indices are also constructed, but are not satisfactory cost-of-living indices in this context. Cost-of-living indices are computed for different income groups, and the impact of inflation in recent years is found to be negatively correlated with income.
Keywords: Consumer prices; Inflation; Cost of living indices; Ireland